The Relationship of Budget Target, Budget Emphasis, and Ethics on Budget Gaps - Hidyatussadhikin, Jumadil Saputra, Murhaban, Rayyan Firdaus, M. Natsir Mahmud Nur, (Opción, 2019)
This study aims to determine the effect of budget target clarity,budget emphasis, and ethics on the budget gaps via a multiple linearregression analysis performed by using SPSS 23. The results indicatethat budget target clarity and ethics has a significant negative effect onthe budget gaps while the budget emphasis has a significant positiveeffect on the budget gaps. In conclusion, a good, specific andmeasurable budget target clarity can reduce the emergence of budgetgaps in the SKPD of Lhokseumawe City.